Congress of Neurological Surgeons Systematic Review and Evidence-Based Guidelines on the Treatment of Pediatric Hydrocephalus: Update of the 2014 Guidelines. Issue 6 (28th October 2020) - Bauer, David F; Baird, Lissa C; Klimo, Paul; Mazzola, Catherine A; Nikas, Dimitrios C; Tamber, Mandeep S; Flannery, Ann Marie
ABSTRACT: BACKGROUND: The Congress of Neurological Surgeons reviews its guidelines according to the Institute of Medicine's recommended best practice of reviewing guidelines every 5 yrs. The authors performed a planned 5-yr review of the medical literature used to develop the "Pediatric hydrocephalus: systematic literature review and evidence-based guidelines" and determined the need for an update to the original guideline based on new available evidence. OBJECTIVE: To perform an update to include the current medical literature for the "Pediatric hydrocephalus: systematic literature review and evidence-based guidelines", originally published in 2014. METHODS: The Guidelines Task Force used the search terms and strategies consistent with the original guidelines to search PubMed and Cochrane Central for relevant literature published between March 2012 and November 2019. The same inclusion/exclusion criteria were also used to screen abstracts and to perform the full-text review. Full text articles were then reviewed and when appropriate, included as evidence and recommendations were added or changed accordingly. RESULTS: A total of 41 studies yielded by the updated search met inclusion criteria and were included in this update. CONCLUSION: New literature resulting from the update yielded a new recommendation in Part 2, which states that neuro-endoscopic lavage is a feasible and safe option for the removal of intraventricular clots and may lower the rate of shunt placement (Level III). Additionally a recommendation in part 7 of the guideline now states that antibiotic-impregnated shunt tubing reduces the risk of shunt infection compared with conventional silicone hardware and should be used for children who require placement of a shunt (Level I). <https://www.cns.org/guidelines/browse-guidelines-detail/pediatric-hydrocephalus-guideline >